Oral health-related quality of life in youth receiving cleft-related surgery: self-report and proxy ratings - Broder, Hillary L.; Wilson-Genderson, Maureen; Sischo, Lacey (Quality of life research, 2017)
Purpose This paper evaluated the impact of cleft-related surgery on the oral health-related quality of life (OHRQoL) of youth with cleft over time. Methods Data were derived from a 5-year, multi-center, prospective, longitudinal study of 1196 youth with cleft lip and/or palate and their caregivers. Eligible youth were between 7.5 and 18.5 years old, spoke English or Spanish, and were non-syndromic. During each observational period, which included baseline, and 1- and 2-year postbaseline follow-up visits, youths and their caregivers completed the Child Oral Health Impact Profile, a validated measure of OHRQoL. Multilevel mixed-effects models were used to analyze the effects of receipt of craniofacial surgery on OHRQoL over time. Results During the course of this study a total of 516 patients (43 %) received at least one surgery. Youth in the surgery recommendation group had lower self (β = -2.18, p < 0.05) and proxy-rated (β = -2.92, p < 0.02) OHRQoL when compared to non-surgical selfand proxy-rated OHRQoL at baseline. Both surgical and non-surgical youth (β = 3.73, p < 0.001) and caregiver (β = 1.91, p < 0.05) ratings of OHRQoL improved over time. There was significant incremental improvement (time × surgery interaction) in self-reported OHRQoL for youth postsurgery (β = 1.04, p < 0.05), but this postsurgery increment was not seen in the caregiver proxy ratings. Conclusions Surgical intervention impacts OHRQoL among youth with cleft. Youth who were surgical candidates had lower baseline self- and caregiver-rated OHRQoL when compared to non-surgical youth. Youth who underwent cleft-related surgery had significant incremental improvements in self-rated but not caregiver (proxy)-rated OHRQoL after surgery.